Three essays on development economics and human capital - KHANNA, Arpita (Institutional Knowledge at Singapore Management University, 2022)
In the first chapter, we estimate the impact of exposure to the 2015 Nepal Earthquake on intimate partner violence with two rounds of Demographic and Health Surveys data. Using differences-in-differences estimation, we find that exposure to the earthquake lead to a statistically and economically significant increase in intimate partner violence in the urban areas but not in the rural areas. This is possibly due to an increase in the stress felt by the victims. We also offer some evidence that the impact heterogeneity between the urban and rural areas is attributable to the differences in the reconstruction processes and assistance provided. The second chapter considers the long term consequences of the Bengal famine of 1943-44 on its survivors about 60 years later. Using World Health survey (WHS) data from Bangladesh and the Indian state of West Bengal and applying differences-in-differences methodology, I find that those with exposure to more intense famine reported having significantly higher number of symptoms of diseases such as asthma, angina, TB and depression. In addition, they were significantly more likely to face difficulty with their daily life activities. However, the results are almost entirely concentrated among females with males showing almost no negative long term impact of the famine. An investigation of possible mechanisms explaining this gender disparity point towards mortality selection among males being more relevant in explaining the disparity as opposed to son preference hypothesis. The third chapter explores the causal impact of the mid day meal program on parental investment in education for primary school going children in India. Using the first round of the Indian Human Development Survey (IHDS) and exploiting the staggered implementation of the mid day meal program across different states in India, we find that the amount spent on school fees reduces significantly by 16 percent for children who are eligible to receive the mid day meal. The significant decrease in school fees can, in part, be attributed to parents transferring their children from private to government schools. We further find that such transfers do not lead to any improvement in learning or health outcomes. However, we do not find any evidence of gender discrimination in school expenditures that might adversely affect the girl child.